Effects of algal sedimentation and Monoporeia affinis on nutrient fluxes, pore water profiles and denitrification in sediment microcosms - Autio, L.; Mäkelä, K.; Lehtonen, K. K.; Kuparinen, J.; Haahti, H. (Boreal Environment Research Publishing Board, 2024)
A flow-through experiment was conducted to study the effects of a simulated algal sedimentation (8.0 g C m-2) and the amphipod Monoporeia affinis (5000 ind. m-2) using well-oxidised sediment from the Gulf of Bothnia. Pore water nutrient profiles, nutrient fluxes, sediment denitrification and O2 consumption as well as NH4+ excretion of M. affinis were followed for 7 days. After the algal enrichment, the NO3- concentration fell to near zero in the pore water and a decrease in the denitrification rate was observed. This occurred since the concentration of NO3- in the flow-through water was low and coupled nitrification-denitrification formed the main denitrification pathway. The share of denitrification compared to other loss processes of N from the sediment reduced from 37% in the control cores to 0.7% in the algae treated cores. The efflux of NH4+ from the sediment formed 99% of the total loss of N in the algae treated cores. A massive efflux of NH4+ and PO43- was observed after the algal enrichment. The amphipods did not increase denitrification.